ASSESSMENT OF GENETIC PARAMETERS OF MAINTAINER LINES FOR HIGH OUT CROSS AND QUALITY THROUGH MORPHOLOGICAL TRAITS IN RICE (Oryza sativa L.) - KASANABOINA KRISHNA; Y. CHANDRA MOHAN; V. GOURI SHANKAR; CH. V. DURGA RANI; L. KRISHNA (The Bioscan, 2020)
An investigation was carried out to study the genetic variability, heritability and genetic advance for 18 traits in 40 genotypes of rice during Kharif, 2018. Analysis of variance revealed that significant differences for all 18 characters studied. Magnitudes of phenotypic and genotypic coefficients of variation were high for number of grains per panicle (37.2 % and 34.1 %), followed by the gel consistency (28.2 % and 27.4 %) and 1000-grain weight (24.9 % and 24.4 %). High heritability coupled with high genetic advance as percent of mean was observed for number of effective tillers per plant, number of grains per panicle, 1000-grain weight, grain yield per plant, kernel length, kernel breadth, kernel L/B ratio, amylose content, gel consistency and kernel length after cooking indicated that these traits were controlled by additive type of gene action in the inheritance. These characters can be further improved by following a simple selection procedure. Whereas the remaining traits, days to 50% flowering, plant height, panicle length, angle of flower opening, stigma exertion, hulling percentage, head rice recovery and milling percentage were controlled by non-additive type of gene action, based on their moderate and low genetic advance as percent of mean respectively.